The Relationship Between Capital Structure and Performance in Islamic Rural Bank - Rofiul Wahyudi; Annisa Fithria; Sartini Wardiwiyono (Universitas Ahmad Dahlan, 2020)
The source of Islamic banking capital must avoid interest as the vision and mission that relies on al-Quran and hadith. The capital structure is important for financial institutions, including Sharia Rural Bank (BPRS). However, BPRS has a problem that is the limited capital owned so that it affects performance. This paper's main objective is to investigate the relationship between capital structure and performance of the Islamic Rural Banks (BPRS) in Indonesia. The study using panel data regression to measure the capital structure on performance. The research sample used 164 BPRS that operate in 33 provinces from 2010 until 2017. The results show that capital structure affects DER (debt to equity ratio) and DAR (debt to asset ratio) but negatively affects ETA (equity to total Asset ratio). These findings indicate an increase in the capital structure of the performance of the BPRS in Indonesia. Hence, bank managers must reach a trade-off between the advantages and disadvantages of creating liquidity and consider the negative relationship between liquidity creation and bank performance when making decisions.